SP0093 The challenges and solutions for engaging patients from ethnic backgrounds in rheumatology care. (15th June 2017) - Kumar, K
Abstract : Rheumatoid Arthritis (RA) is a condition with no cure and can cause disability 1 . RA affects nearly 1 in 100 adults. Early disease is characterised by pain and other features of inflammation, such as heat, swelling of joints, and loss of function. RA is associated with increased costs of co-morbid conditions (such as cardiovascular (CVD) associated with RA 2 . CVD associated with RA is the most common cause of death in RA patients. The risk of developing CVD is worse in some ethnic groups 3;3;4 . Furthermore, RA causes physical damage and social, economic, psychological and cultural problems that impact on all aspects of patient life. There are effective treatments available for RA 5 ; however, non-adherence to medicines (not taking medicines as prescribed) is a significant issue in RA 6 . Patients' perceptions play an important role in adherence to medicines. Our research in the UK, has showed differences between individuals from ethnic groups on how they view their medicines 7 . These views can potentially impact on medication adherence and patients' satisfaction with information they receive in clinic. In the UK, we have recently shown that patients from different ethnic backgrounds with RA were disstaified with the information they receive about medicines 7 . Patients beliefs about medicines and illness pereceptions were found to be associated with satisfaction with information received by clinicans. Furthermore, the British Society of Rheumatology (BSR) led a national audit to investigate the delivery of care across UK rheumatology services. In this audit of early inflammatory arthritis service, we found patients from different ethnic backgrounds expressed greater impact of the disease on functional disability, fatigue, emotional well-being, physical well-being and coping and worse in older patients. This can impact on the way patients perceive their disease activity and information received on treatments. If we understand the needs of patients from ethnic backgrounds we can help improve the health outcomes. This session will provide the audience with insight into some solutions from the UK that might be helpful in order to improve satisfaction with information, disease enagement and treatment adherence. References: Emery P. Evidence supporting the benefit of early intervention in rheumatoid arthritis. J Rheumatol, 2002;29 (2):3–8. John H, Kitas G, Toms T, Goodson N. Cardiovascular co-morbidity in early rheumatoid arthritis. Best Pract Res Clin Rheumatol 2009; 23(1):71–82. Grover S, Sinha RP, Singh U, Tewari S, Aggarwal A, Misra R. Subclinical atherosclerosis in rheumatoid arthritis in India. J Rheumatol 2006; 33(2):244–247. Chung CP, Giles JT, Petri M, Szklo M, Post W, Blumenthal RS et al. Prevalence of traditional modifiable cardiovascular risk factors in patients with rheumatoid arthritis: comparison with control subjects from the multi-ethnic study of atherosclerosis. Semin Arthritis Rheum 2012; 41(4):535–544. Smolen JS, Landewe R, Breedveld FC, Buch M, Burmester G, Dougados M et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update. Ann Rheum Dis 2014; 73(3):492–509. Pasma A, Schenk CV, Timman R, Busschbach J, van den bemt B, Molenaar E et al. Non-adherence to disease-modifying antirheumatic drugs is associated with higher disease activity in early arthritis patients in the first year of the disease. Arthritis Research & Therapy 2015; 17:doi:10.1186/s13075–015–0801–4. Kumar K, Raza K, Nightingale P, Horne R, Chapman S, Greenfield S et al. Determinants of adherence to disease modifying anti-rheumatic drugs in White British and South Asian patients with rheumatoid arthritis: a cross sectional study. BMC Musculoskelet Disord 2015; 16(1):396. Disclosure of Interest: None declared